DksA-Dependent Transcriptional Regulation in Salmonella Experiencing Nitrosative Stress - Crawford, Matthew A.; Henard, Calvin A.; Tapscott, Timothy; Porwollik, Steffen; McClelland, Michael; Vázquez-Torres, Andrés (Frontiers in Microbiology, 2016)
Redox-based signaling is fundamental to the capacity of bacteria to sense, and respond to, nitrosative and oxidative stress encountered in natural and host environments. The conserved RNA polymerase regulatory protein DksA is a thiol-based sensor of reactive nitrogen and oxygen species. DksA-dependent transcriptional control promotes antinitrosative and antioxidative defenses that contribute to Salmonella pathogenesis. The specific adaptive changes mediated by DksA in response to reactive species, however, have not been elucidated. Herein, we characterize DksA-dependent changes in gene expression in Salmonella enterica experiencing nitrosative stress. Genome-wide expression analysis of wild-type and delta-dksA Salmonella exposed to the nitric oxide (•NO) donor DETA NONOate demonstrated •NO- and DksA-dependent regulatory control of 427 target genes. Transcriptional changes centered primarily on genes encoding aspects of cellular metabolism. Several antioxidants and oxidoreductases important in redox buffering, •NO detoxification, and damage repair were also observed to be up-regulated in an •NO- and DksA-dependent manner. Compared to wild-type bacteria, •NO-treated delta-dksA Salmonella exhibited a de-repression of genes encoding components of iron homeostasis and failed to activate sulfur assimilation and cysteine biosynthetic operons. As cysteine is integral to efficient antinitrosative and antioxidative defense and repair programs, we further examined the redox-responsive transcriptional control of cysteine biosynthesis by DksA. These investigations revealed that the activation of genes comprising cysteine biosynthesis also occurs in response to hydrogen peroxide, is dependent upon the redox-sensing zinc finger domain of DksA, and requires the transcriptional regulator CysB. Our observations demonstrate that DksA mediates global adaptation to nitrosative stress in Salmonella and provide unique insight into a novel regulatory mechanism by which cysteine biosynthesis is controlled in response to reactive oxygen and nitrogen species.